Invertebrates - Ecophysiology and Management 2020
DOI: 10.5772/intechopen.85842
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Host Snails of Human Schistosomes in the Senegal River Delta: Spatial Distribution According to Physicochemical Parameters

Abstract: The objective of the study was to evaluate the influence of physicochemical parameters of water on the spatial distribution of snail intermediate hosts of human schistosomes in the Senegal River Delta. Eight water points in three endemic villages for schistosomiasis were selected for biweekly monitoring of snail numbers and physicochemical parameters of water at the beginning of the rainy season. The results show that the spatial distribution of snail populations is a function of certain parameters. The pH, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Freshwater snails prefer habitats with pH levels ranging from 6.5-8.5 as extreme pH levels increase the solubility of elements and compounds making toxic chemicals more mobile and increasing the risk of absorption by aquatic life and leading to death. In this study, snails were found in sites with pH levels ranging from 6.42-7.98, which falls within the favorable range for surface water [38]. A significant positive correlation was recorded between pH, B. globosus, and T. granifera, while a negative correlation was recorded with B. tropicus, B. forskalii, L. natalensis, bivalves, and P. acuta.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Freshwater snails prefer habitats with pH levels ranging from 6.5-8.5 as extreme pH levels increase the solubility of elements and compounds making toxic chemicals more mobile and increasing the risk of absorption by aquatic life and leading to death. In this study, snails were found in sites with pH levels ranging from 6.42-7.98, which falls within the favorable range for surface water [38]. A significant positive correlation was recorded between pH, B. globosus, and T. granifera, while a negative correlation was recorded with B. tropicus, B. forskalii, L. natalensis, bivalves, and P. acuta.…”
Section: Discussionsupporting
confidence: 52%
“…This could be because there were heavy rains prior to sampling and hence floods or fast flowing water may have swept away many freshwater snails and food causing major fluctuations in the population density [36]. In addition, snail abundance and diversity reduce with high rainfall as snails cannot attach themselves to rocks or water vegetation and are washed away by the high velocities (>0.3 ms −1 ) of flowing water [37,38]. On the other hand, B. globosus, B. forskalii, and T. granifera showed a positive correlation, and this could be because of snail abundance and diversity increase with low rainfall or at the beginning of the rainy season [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of Bulinus and Physa was positively correlated although Physa was the most abundant freshwater snail species in Tiko. Some studies have shown a positive correlation between other freshwater snails ( Tarebia granifera ) and Bulinus globosus [ 67 , 68 ] whereas a recent study showed a negative correlation, though not significant, between B . globosus and the invasive Physa acuta [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of Bulinus and Physa was positively correlated although Physa was the most abundant freshwater snail species in Tiko. Some studies have shown a positive correlation between other freshwater snails (Tarebia granifera) and Bulinus globosus [67,68] whereas a recent study showed a negative correlation, though not significant, between B. globosus and the invasive Physa acuta [69]. This finding has implication for further investigation as research has shown that P. acuta has higher fecundity, shorter hatching time, higher salinity tolerance, higher temperature tolerance, and tolerates fast current velocities up to 0.6 ms -1 compared to other pulmonates that are not found in water exceeding the velocity of 0.3 ms -1 [70].…”
Section: Plos Onementioning
confidence: 99%